Antiobesity potential of Aconitum Heterophyllum roots - JAIN SURENDRA KUMAR,; JAIN RUCHI,; JAIN NILESH, (International Journal of Pharma and Bio Sciences, 2019)
Obesity, the chronic metabolic disorder resulting from the imbalance between energy intake and energy expenditure, the characteristics of it are, enlarged fat mass and elevated lipid concentration in blood. Aconitum Heterophyllumis an indigenous medicinal plant of India and belongs to the family Ranunculaceae. A. Heterophyllum is known to possess a number of therapeutic effects. For very ancient times, this plant has been used in some formulations in the traditional healing system of India. In the present study, the Anti-obesity activity of successive solvent extract by petroleum ether, chloroform and ethanol of A. heterophyllum are reported. The ethanolic extract of A. heterophyllum was orally administered in high-fat high cholesterol diet (HFHCD) obese rats for about 12-14 weeks. After four weeks of treatment, blood samples were collected for the estimation of serum lipids, glucose, Total Cholesterol, HDL, LDL and Triglycerides. The A. heterophyllum treatment markedly lowered total cholesterol, triglycerides in blood serum. It also showed positive effects (increase) on serum high-density lipoprotein cholesterol (HDL-c) concentrations. Presence of flavonoids, alkaloids, tannins and steroids may be responsible for its antiobesity activity. The results demonstrated that feeding with High Fatty Diet had caused a significant increase in weight gain compared with the zero-day activity, which was significantly decreased by the co-administration of A. Heterophyllum especially Alcoholic Extract of A. Heterophyllume (AAH) in a dose-dependent manner. Thus the present findings emphasize that the roots of A. Heterophyllum possesses potential medicinal values.